2001
DOI: 10.1099/00221287-147-12-3215
|View full text |Cite
|
Sign up to set email alerts
|

Twitching motility of Ralstonia solanacearum requires a type IV pilus system

Abstract: Twitching motility is a form of bacterial translocation over firm surfaces that requires retractile type IV pili. Microscopic colonies of Ralstonia solanacearum strains AW1, K60 and GMI1000 growing on the surface of a rich medium solidified with 16 % agar appeared to exhibit twitching motility, because early on they divided into motile ' rafts ' of cells and later developed protruding ' spearheads ' at their margins. Individual motile bacteria were observed only when they were embedded within masses of other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(146 citation statements)
references
References 68 publications
2
142
1
Order By: Relevance
“…They bear Walker A (motif I) and B (motif II or DExx box) NTP-binding sequences [88] and may use the energy of Rhizobium etli bacterium; N2-fixation [154] Sinorhizobium meliloti bacterium; N2-fixation [14,15,17] Shigella flexneri plasmid ColIb P9 bacterium; diarrhoea / dysentery [155] Bartonella henselae and tribocorum bacterium; cat scratch disease, bacteremia [156][157][158][159][160] Campylobacter jejuni bacterium; bacterial diarrhoea [161,162] Toxoplasma gondii protozoon; toxoplasmosis (encephalitis) [54] Leishmania donovani protozoon; leishmaniasis [54] Mycobacterium tuberculosis bacterium; tuberculosis [54] Bordetella bronchiseptica bacterium; bronchitis [14,15,17] Enterobacter aerogenes bacterium; nosocomial infections [11] Actinobacillus actinomycetemcomitans bacterium; periodontitis [14,15,17,163,164] Escherichia coli bacterium; diarrhea [11] Caulobacter crescentus bacterium; non-pathogenic [14,15,17] Coxiella burnetii bacterium; acute febrile disease, endocarditis, pneumonitis [165,166] Thiobacillus ferroxidans bacterium; iron oxidation [14,15,17] Wolbachia intracellular symbiont of arthropods; sexual alterations in host [167,168] Ralstonia eutrophantus bacterium; heavy-metal resistance [11,169] Salmonella typhi, typhimurium and enteriditis bacterium; typhus, salmonellosis …”
Section: Transfer Factors In Conjugative Type-iv Secretionmentioning
confidence: 99%
“…They bear Walker A (motif I) and B (motif II or DExx box) NTP-binding sequences [88] and may use the energy of Rhizobium etli bacterium; N2-fixation [154] Sinorhizobium meliloti bacterium; N2-fixation [14,15,17] Shigella flexneri plasmid ColIb P9 bacterium; diarrhoea / dysentery [155] Bartonella henselae and tribocorum bacterium; cat scratch disease, bacteremia [156][157][158][159][160] Campylobacter jejuni bacterium; bacterial diarrhoea [161,162] Toxoplasma gondii protozoon; toxoplasmosis (encephalitis) [54] Leishmania donovani protozoon; leishmaniasis [54] Mycobacterium tuberculosis bacterium; tuberculosis [54] Bordetella bronchiseptica bacterium; bronchitis [14,15,17] Enterobacter aerogenes bacterium; nosocomial infections [11] Actinobacillus actinomycetemcomitans bacterium; periodontitis [14,15,17,163,164] Escherichia coli bacterium; diarrhea [11] Caulobacter crescentus bacterium; non-pathogenic [14,15,17] Coxiella burnetii bacterium; acute febrile disease, endocarditis, pneumonitis [165,166] Thiobacillus ferroxidans bacterium; iron oxidation [14,15,17] Wolbachia intracellular symbiont of arthropods; sexual alterations in host [167,168] Ralstonia eutrophantus bacterium; heavy-metal resistance [11,169] Salmonella typhi, typhimurium and enteriditis bacterium; typhus, salmonellosis …”
Section: Transfer Factors In Conjugative Type-iv Secretionmentioning
confidence: 99%
“…It has been observed mostly in saprophytic bacteria and mammalian pathogens. Such motility in plant-associated bacteria has been observed in Ralstonia solanacearum (Kang et al, 2002;Liu et al, 2001) and X. fastidiosa (Meng et al, 2005). To date, approximately 40 genes have been identified that are involved in the biogenesis and function of type IV pili in Pseudomonas aeruginosa (Mattick, 2002), including the genes that encode the major structural protein (PilA), and those that encode the minor proteins involved in formation of the base and/or tip of the pilus, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, soaking plantlets in suspensions of nonphytopathogenic P. putida ATCC 12633 or media alone also caused wilting. Moreover, we found that after 36 A hallmark of nearly all plant-pathogenic bacteria is the ability to produce a hypersensitive response in tobacco (13,23,79). Tobacco leaves infiltrated with 10 9 cells ml Ϫ1 of B. thailandensis or P. putida did not elicit a hypersensitive response after 7 days, while those infiltrated with the same amount of R. solanacearum developed a hypersensitive response after 2 days.…”
Section: Figmentioning
confidence: 83%
“…Escherichia coli, B. pseudomallei, and B. thailandensis were grown at 37°C in Luria-Bertani medium (LB) (42), LB supplemented with 2% glycerol (LBG), or M9 medium (57) with 20 mM glutamate instead of glucose. R. solanacearum and Pseudomonas putida were grown at 30°C in 1% Bacto peptone, 0.1% Casamino Acids, 0.1% yeast extract, and 0.5% glucose (BG) (36). When necessary, antibiotics were used at the following concentrations: kanamycin at 50 g/ml (Km 50 ) for Burkholderia spp.…”
Section: Methodsmentioning
confidence: 99%